Sex-related differences in the maximal lactate steady state - Hafen, P. S.; Vehrs, P. R. (Sports, 2018)
The maximal lactate steady state (MLSS) is one of the factors that differentiates performance in aerobic events. The purpose of this study was to investigate the sex differences in oxygen consumption (VO2), heart rate (HR), and the respiratory exchange ratio (RER) at the MLSS in well-trained distance runners. Twenty-two (12 female, 10 male) well-trained distance runners (23 ± 5.0 years) performed multiple 30-min steady-state runs to determine their MLSS, during which blood lactate and respiratory gas exchange measures were taken. To interpret the MLSS intensity as a training tool, runners completed a time-to-exhaustion (TTE) run at their MLSS. The relative intensity at which the MLSS occurred was identical between males and females according to both oxygen consumption (83 ± 5 %O2max) and heart rate (89 ± 7 %HRmax). However, female runners displayed a significantly lower RER at MLSS compared to male runners (p < 0.0001; 0.84 ± 0.02 vs. 0.88 ± 0.04, respectively). There was not a significant difference in TTE at MLSS between males (79 ± 17 min) and females (80 ± 25 min). Due to the observed difference in the RER at the MLSS, it is suggested that RER derived estimates of MLSS be sex-specific. While the RER data suggest that the MLSS represents different metabolic intensities for males and females, the relative training load of MLSS appears to be similar in males and female runners